2005
DOI: 10.1002/jsfa.2373
|View full text |Cite
|
Sign up to set email alerts
|

Influence of growth stage and postharvest storage on ascorbic acid and carotenoid content and visual quality of baby spinach (Spinacia oleracea L.)

Abstract: To investigate the variations in quality with growth stage and postharvest storage, spinach was sown on three occasions. For each occasion, the spinach was harvested at three growth stages at 6‐day intervals. The second stage corresponded to a growth period used for baby spinach by commercial growers. After harvest, the leaves were stored in polypropylene bags at 2 °C or 10 °C. The highest ascorbic acid content in fresh material was found at stage I. During storage, the ascorbic acid content decreased consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
71
4
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(96 citation statements)
references
References 59 publications
20
71
4
1
Order By: Relevance
“…Olaofe (1992) on the other hand, reported that decreased in vitamin C concentration during refrigerated storage is partly due to the enzymatic activities of vitamin C oxidase, cytochrome oxidase and vitamin C peroxidase that were endogenously present. The findings agreed with the report of Bergquist et al (2006) that during freezing of vegetables the ascorbic acid concentration decreased considerably and the dehydroascorbic acid/vitamin C ratio increased. The generally insignificant differences recorded in the β-carotene concentration in second to fourth weeks and vitamin C content in first to fourth week of storage could be seen as a result of decrease in endogenous enzymatic activity and reduction of oxidation of the compound as freezing storage progresses.…”
Section: Discussionsupporting
confidence: 92%
“…Olaofe (1992) on the other hand, reported that decreased in vitamin C concentration during refrigerated storage is partly due to the enzymatic activities of vitamin C oxidase, cytochrome oxidase and vitamin C peroxidase that were endogenously present. The findings agreed with the report of Bergquist et al (2006) that during freezing of vegetables the ascorbic acid concentration decreased considerably and the dehydroascorbic acid/vitamin C ratio increased. The generally insignificant differences recorded in the β-carotene concentration in second to fourth weeks and vitamin C content in first to fourth week of storage could be seen as a result of decrease in endogenous enzymatic activity and reduction of oxidation of the compound as freezing storage progresses.…”
Section: Discussionsupporting
confidence: 92%
“…The AA could be attributed mainly to vitamin C, but also to several compounds such as fibres, polymeric polyphenols and other phytonutrients 46. However, spinach AA and also total phenolics content, are influenced by genetics, growing season and minimal processing 47, 48. It is remarkable that the highest initial amount was found for 8 mmol N L −1 and no differences were found for the remaining N fertilisations.…”
Section: Resultsmentioning
confidence: 97%
“…2007). Furthermore, Bergquist et al. (2006) have shown that total carotenoids content increased or remained stable during storage in spinach.…”
Section: Resultsmentioning
confidence: 98%